You are on page 1of 13

# SMK CONVENT BUKIT NANAS, KUALA LUMPUR.

YEAR 2012
TEST 1: ADDITIONAL MATHEMATICS FORM 4
Time: 1 ½ HOUR

NAME: .................................................................................. FORM : 4 ...................

Instruction to candidates:

This paper consists of 18 questions. Answer all questions. Write your answer clearly in the spaces provided
erase the answer that you have done. Then write down the new answer. The diagrams in the questions
provided are not drawn to scale unless stated. The marks allocated for each question are shown in brackets.
This question paper must be handed in at the end of examination.

1.
Given that 7m + 2n = 9 and 6m + n = 7, find the value of m and n.

2.
FF Diagram 1 shows the relation between set A and set B in the arrow diagram.

Diagram 1

Diagram 2 shows the relation between set S and set T in the arrow diagram.a) State the type of the relation. Answer: 3. [2 marks] b) Object(s) of p. Diagram 2 State the ( image of 12 a ) (b) object of 7 (c) domain of this relation (d) range of this relation [4 marks] Answer: .

Given function f : x → 3x + 6. Diagram 3 State the relation in the form of ordered pairs.4. (b) Sketch the graph of f(x) for the domain −2 ≤ x ≤ 2. find the a) image of -7 b) object when image is 15 Answer: [3 marks] 6 Given the function f : x → |2x + 2|. [4 marks] Answer: . [2 marks] Answer: 5. Diagram 3 shows the relation between set X and set Y in the graph form. (a) Find the images of −2. 0 and 2.

5 [3 marks] Answer: 9 The functions of u and v are defined as u: x → x − 3 and v : x → x2 − 6. find the value of (a) f(120°) (b) x when f(x) = 0. 0° ≤ x ≤ 180°. Find the composite function 7 of gf and the value of gf(2). [4 marks] . [3 marks] Answer: 8 Given function f : x → cos x. The functions of f and g are defined as f : x → x − 4 and g : x → . Find the composite function of uv and vu.

[2 marks] Answer: 11 The functions of f and g are defined as f : x → x + 6 and gf : x → 3x + 8. Find the function g. Answer: 10 The functions of f and g are defined as f : x → x + 4 and fg : x → 2x − 7. x ≠ a. The functions of h and k are defined as h: x → x + 9 and k : x → . Find the function g. Find (a) the value of a (b) the composite function h2 . [3 marks] Answer: 12.

(c) the composite function kh [4 marks] Answer: 13 The function f is defined as f : x → 4x + 3. Find gf−1(x). Find (a) f−1(x) (b) f−1(7) [3 marks] Answer: 14 The functions f and g are defined as f : x → 4 − 2x and g : x → 5x + 3. [3 marks] Answer: .

Diagram 4 Find the (a) values of b and c. Find (a) g(x) (b) the value of x when f 2(x) = 2.15 Given the function f : x → 3x – 4 and the composite function fg : x → 5 – 6x. (b) the image of −9 under the function. [5 marks] Answer: . [4 marks] Answer: 16 Diagram 4 represents a function f: x → x2 + bx + c.

17 2 Given h (x) → 3 x  5 find h(x). Answer: [3 marks] . −1 Answer: [4 marks] 18 3  2x Given g(x) → 4 find -1 a) g (x) . Hence evaluate h(2). b) the value of x if g(x) maps to itself.

Miss. Sazlin Aina bt Abd.... Maths... Ghani Ms. (2. 14)} 5 (a) f(−7) = 3(−7) + 6 = −15 (b) f(x) = 15 3x + 6 = 15 3x = 9 x=3 6 (a) f(x) = |2x + 2| ... Gan Fei Ting Coordinator of Form 4 Add.... .......... (2..... END OF THE QUESTION PAPER Prepared by: Checked by: . Head of Panel of Add... (2....... -5m = -5 m=1 use EQ 1 to find t 7(1) + 2n = 9 2n = 2 n=1 2 Many-to-one relation 3 (a) 2 (b) 14 (c) {12....... (7....... 16)...... 8).................. 7} 4 {(2.......... Marking Scheme and Answers for ADDITIONAL MATHEMATICS FORM 4 TEST 1 1 7m + 2n = 9  EQ 1 12m +2n = 14  EQ 2 EQ 1 – EQ 2.. (5... 14} (d) {2. 14)......... Maths.. 20). 20)....

5 cos x = 0.5 x = 60° 9 Given u(x) = x − 3 and v(x) = x2 − 6. f(−2) = |2(−2) + 2| = |−4 + 2| = |−2| =2 f(0) = |2(0) + 2| = |2| =2 f(2) = |2(2) + 2| = |4 + 2| = |6| =6 (b) f(x) = 0 |2x + 2|= 0 2x + 2 = 0 x = −1 7 Given f(x) = x − 4 and g(x) = . gf(x) = g(f(x)) = g(x − 4) = gf(2) = =− 8 (a) f : x → cos x f(120°) = cos 120° = −0. uv(x) = u(v(x)) = u(x2 − 6) = (x2 − 6) − 3 = x2 − 9 vu(x) = v(u(x)) = v(x − 3) = (x − 3)2 − 6 = (x2 − 6x + 9) − 6 = x2 − 6x + 3 .5 (b) f(x) = 0.

gf(x) = g(f(x)) = g(x + 6) g(x + 6) = 3x + 8 Let y = x + 6 So. f−1(x) = 14 Let f−1(x) = y So f(y) = x 4 − 2y = x . f−1(7) = 1 (b) Let f−1(x) = y So f(y) = x 4y + 3 = x 4y = x − 3 y= Therefore. fg(x) = f(g(x)) = g(x) + 4 g(x) + 4 = 2x − 7 g(x) = 2x − 11 ∴ g : x → 2x − 11 11 Given f(x) = x + 6 and gf(x) = 3x + 8. x = g(y) = 3 + 8 = 3y − 10 Therefore. g : x → 3x − 10 12 (a) x − 2 = 0 x=2 ∴a = 2 (b) h2 = h(h(x)) = h(x + 9) = (x + 9) + 9 = x + 18 (c) kh(x) = k(h(x)) = g(x + 9) = = . x ≠ −7 13 (a) Let f−1(7) = k So f(k) = 7 4k + 3 = 7 k=1 Therefore.10 Given f(x) = x + 4 and fg(x) = 2x − 7.

g : x → 3-2x (b) ff(x) = 3(3x-4)-4 = 2 9x-12-4 = 2 x=2 16 f(x) = x2 + bx + c f(2) = 13 (2)2 + b(2) + c = 13 4 + 2b + c = 13 2b + c = 9 −−−− E1 f(3) = 26 (3)2 + b(2) + c = 26 9 + 3b + c = 26 3b + c = 17 −−−− E2 E1 − E2: −b = −8 b=8 Substitute b = 8 into E1. 2(8) + c = 9 c = −7 f(x) = x2 + 8x − 7 f(−9) = (−9)2 + 8(−9) − 7 = 81 − 72 − 7 =2 17 Let h−1(x) = y So h(y) = x 2 3x  5 = y 2  5y x 3y .6x . fg(x) = f(g(x)) 5-6x = 3g(x) – 4 Therefore. y= Therefore f−1(x) = gf−1(x) = g(f−1(x)) = g() = 5() + 3 = 15 (a) Given f(x) = 3x .4 and fg(x) = 5 .

x  0 Therefore. 3  2x x 4 1 x= 2 . g-1(x) = 2 When g(x) = x. 2  5x . h(x) = 3x 18 Let g−1(x) = y So g(y) = x 3  2y x 4 3  4x y 2 3  4x Therefore.